Strategies used to Motivate Teachers in Kenya: A case of Rural and Urban Primary Schools in Embu and Kirinyaga Counties, Kenya - A.M , Ngare; J.N , Njoka; J.M , Mwaruvie; J.M , Mwaruvie, (African Journal of Education,Science and Technology (AJEST), 2021)
Teachers play fundamental role in the development of human resource in the world. The motivation of teachers significantly influences their effectiveness in the quest of producing desired educational outcomes in learners. The purpose of this study was to assess the strategies used to motivate teachers in rural and urban primary schools in Embu and Kirinyaga in Kenya. The objective of the study was to examine the strategies used to motivate teachers in rural and urban primary schools in Embu and Kirinyaga counties. It was hypothesized that there is no statistically significant difference in motivation among teachers in rural and urban primary schools in Embu and Kirinyaga counties. The study adopted a descriptive survey research design and the target population consisted of 583 primary schools distributed as follows, rural (464) and urban (119). A sample of (58)10% of the schools was selected from the population and proportionately distributed, thus Rural (38) and urban (20) schools. From each of the sampled schools three (3) teachers were selected one representing the lower, upper primary and the head teacher, thus the sample comprised of 174 respondents. The overall computed mean scores of motivations of teachers for rural schools was (= 3.11) and urban schools ( = 3.08). These mean scores indicated that on general scale rural schools had slightly better motivation strategies compared to urban schools, although the levels of motivation were average in both school categories. Testing the null hypothesis using t-test established that there was no significant difference between the levels of motivation between teachers in rural and urban primary schools. The study recommends the need to investigate the working conditions of teachers, opportunities for career development, remuneration, availability and adequacy of resources and leadership styles in schools as causal factors to low teacher morale in primary schools in Embu and Kirinyaga Counties.